3D reconstruction in underground utilities - Su, Yang; Wang, J.; Wang, Xiangyu; Yao, Y.; Shou, W. (2023)
Underground utilities (UU) play a vital role in modern life. Creating an accurate, up-to-date, and comprehensive digital representation of underground infrastructure has become a top priority for the infrastructure planning, (re)development, construction recording, and safety management of UU projects. However, both industry and academia lack a common understanding of the latest progress, challenges, and decision-making frameworks for UU 3D reconstruction technologies. Therefore, 323 related articles are investigated and provides a scientific basis for selecting different technologies for various scenarios. First, the advantages, limitations, and the best performance of each technique are analyzed. Second, the current applications of UU 3D reconstruction are reviewed. Third, a decision-making framework is proposed for selecting 3D reconstruction technologies to help stakeholders scientifically choose appropriate technology routes. Finally, limitations and future work in this field are discussed.